Hydrosulfonylation of Alkenes with Sulfonyl Chlorides under Visible Light Activation. Issue 28 (7th May 2020) - Hell, Sandrine M.; Meyer, Claudio F.; Misale, Antonio; Sap, Jeroen B. I.; Christensen, Kirsten E.; Willis, Michael C.; Trabanco, Andrés A.; Gouverneur, Véronique
Abstract: Sulfonyl chlorides are inexpensive reactants extensively explored for functionalization, but never considered for radical hydrosulfonylation of alkenes. Herein, we report that tris(trimethylsilyl)silane is an ideal hydrogen atom donor enabling highly effective photoredox‐catalyzed hydrosulfonylation of electron‐deficient alkenes with sulfonyl chlorides. To increase the generality of this transformation, polarity‐reversal catalysis (PRC) was successfully implemented for alkenes bearing alkyl substituents. This late‐stage functionalization method tolerates a remarkably wide range of functional groups, is operationally simple, scalable, and allows access to building blocks which are important for medicinal chemistry and drug discovery. Abstract : Radical new approach : Sulfonyl chlorides have been applied in the radical hydrosulfonylation of alkenes. Tris(trimethylsilyl)silane is an ideal hydrogen atom donor enabling highly effective photoredox‐catalyzed hydrosulfonylation of electron‐deficient alkenes with sulfonyl chlorides. To increase the generality of this transformation, polarity‐reversal catalysis was successfully implemented for alkenes bearing alkyl substituents.